The Study of Ayatollah Mesbah Yazdi’s Philosophical Theory in Comparison with the Issue of “Unity” - Ali Mohammadi; Yahya Abdullahi (اخلاق وحیانی)
The theory of ayatollah Mesbah must be presented through the two issues of “the analysis of ethical deeds” and “the analysis of ethical statements”. With regard to the first issue, ayatollah Mesbah believes that the main and axial drive in human beings is “self-love” and that the goal that provides one’s “self” with its interests, more than anything else, is more loved and favored by him and such a goal is named the “ultimate perfection” whose extension is “nearness to Allah”.  Therefore, the prerequisites that can pave the way for this “nearness” are the worthy and ethical deeds, and those which hinder the achievement of this “nearness” are the immoral deeds. What ayatollah Mesbah means by “prerequisites” is the necessary relationship between the ethical deed and the ultimate perfection. With regard to the second issue (i.e. the analysis of the ethical statements) he considers the issue of “ethical statements” as one of the secondary philosophical concepts, which is inferred from the causal relationships between the “voluntary action” and its result. The second part of the present paper is devoted to the examination of this theory in comparison with the concept of “Unity”.Here, the questions “can one analyze the issues of worshipping and devotion as being the result of “self-love” based on this theory?” and “can varying levels of self-love justify “obeying and disobeying” Allah?” are raised. The study of these two questions is the pursuit of the second part of this paper.